2019
DOI: 10.1097/ijg.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Patient Education Into the Glaucoma Clinical Encounter: A Lean Analysis

Abstract: PURPOSE:To use lean analysis to identify how often and when wait times occur during a glaucoma visit to identify opportunities for additional patient engagement. METHODS:This prospective observational time-motion study measured process and wait times for 77 patient visits from 12 ophthalmologists at an academic glaucoma clinic over a 3-month period. Value stream maps visually diagrammed the process of a clinic visit from the patient's perspective. Descriptive statistics were calculated for process times, wait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In our trial, physician time per patient in the control arm was 3.04 minutes (vs. about 8–10 minutes in US-based glaucoma studies [ 36 , 37 ]). The dramatically lower time per patient at our trial site reflects AECS’s design philosophy: senior doctors perform only those tasks that cannot be performed by junior doctors or other staff [ 38 ].…”
Section: Discussionmentioning
confidence: 67%
“…In our trial, physician time per patient in the control arm was 3.04 minutes (vs. about 8–10 minutes in US-based glaucoma studies [ 36 , 37 ]). The dramatically lower time per patient at our trial site reflects AECS’s design philosophy: senior doctors perform only those tasks that cannot be performed by junior doctors or other staff [ 38 ].…”
Section: Discussionmentioning
confidence: 67%
“…The team created a value-stream visual diagram that incorporates every process in the clinic flow. The team then mapped where the “value” and the “waste” occurred and identified potential areas of improvement [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most studies analyzing the effects of educational interventions on medication adherence have designed interventions focused on eye drop administration technique and patient provider communication by showing patients instructional videos for eye drop administration, 12 videotaping and transcribing clinic visits, 13,14 and assigning trained personnel to counsel patients. 15 Interventions built on patient education and motivational interviewing are hypothesized to have improved glaucoma medication adherence by increasing patient confidence in following medication regimens 14,[16][17][18][19][20] . Carpenter and colleagues found that provider education regarding medication adherence was associated with improved IOP at an eightmonth follow-up.…”
Section: Introductionmentioning
confidence: 99%